PERLINDUNGAN HUKUM BAGI PEKERJA RUMAH TANGGA YANG MENGALAMI TINDAK PIDANA KEKERASAN - Nur Meylawati (2022)
Domestic workers are widely used in Indonesia. PRT is a demanding occupation. This is because being a maid doesn't require any special and certain conditions. However, it is often seen as an outsider and is assigned to marginal or minority groups. The work of the housekeeper includes numerous household chores that can doubtless make it easier for anyone to use a maid. It is not limited to household chores, such as washing, cooking, ironing. However, it may also help to lighten other chores, such as driving, cleaning up the garden. So it's not only female, but male can also be categorized as domestic. Because of her helpful housework. However, many maids do not guarantee protection for the maid itself. Because until now there had been no specific law enforcement to protect a PRT from any forms of discrimination and violence that would very easily threaten a maid. Violence against domestic violence has continued up to this day. The CPRT bill, which existed since seventeen (17) years ago, therefore needed to be passed quickly. In view of forms of violence that can afflict the PRT not only physical and psychic violence, but they can take the form of economic and sexual violence. Therefore, approval of the HLC bill to ensure PRT's rights is urgently needed.